The Trade Effects of the Economic Partnership Agreements between the European Union and the African, Caribbean and Pacific Group of States: Early Empirical Insights from Panel Data* - Frederik Stender; Axel Berger; Clara Brandi; Jakob Schwab (JCMS: Journal of Common Market Studies, 2021)
This study provides early ex-post empirical evidence on the effects of provisionally applied Economic Partnership Agreements (EPAs) on trade flows between the European Union (EU) and the African, Caribbean and Pacific Group of States (ACP). Employing the gravity model of trade, we do not find a general EPA effect on trade between ACP countries and the EU, but identify heterogeneous effects across specific agreements and economic sectors. While the CARIFORUM-EU EPA rather reduced imports from the EU overall, other EPAs seem to have partly increased EU imports, particularly for the Southern Africa Development Community (SADC) EPA partner countries. On the sectoral level, by comparison, we find increases in the EU's agricultural exports to SADC, Eastern and Southern Africa (ESA) and the Pacific. In the area of manufactures trade, we find decreases of exports of the ESA and SADC countries to the EU, but increases in EU imports for SADC countries.
Keywords: 330; Cotonou partnership agreement; Economic Partnership Agreements; EU trade policy; gravity model of trade